Vertical distribution of root biomass and soil carbon stocks in forage cropping systems - Ojeda, Jonathan Jesus; Caviglia, Octavio; Agnusdei, Monica Graciela (Springer, 2018)
Background and aims: Forage cropping systems may differentially affect the vertical distribution of roots and soil organic C stock (C-OM). In annual crops sequences (ACS) and perennial pastures (PP), we assessed the association between root biomass, C-OM, C in mineral-associated organic matter (C-MAOM), and C in particulate organic matter (C-POM) and its vertical distribution. Methods: Root biomass, C-OM, C-MAOM and C-POM were measured in a Petrocalcic Argiudol at five soil depths up to 100 cm during two years in the south-eastern Pampas of Argentina. The field experiment comprised 28 plots including five perennial pastures and two annual crop sequences. Associations between variables were assessed by regression analysis and non-linear models. Results: Overall, ACS and PP had similar cumulative root biomass. Both, root biomass and soil C stocks exponentially decreased with soil depth. Soil C stocks associated to root biomass tended to stabilize over a threshold value of root biomass for C-MAOM and C-OM. C-POM tended to stabilize over a threshold value only in treatments that included tall fescue. Conclusions: Our results highlights the key role of roots to improve soil C stocks through the design of forage crop rotations that include crops able to increase root inputs to the soil, such as tall fescue.